Comparison of doxycycline with azithromycin in treatment of pharyngeal chlamydia infection. (December 2016) - Manavi, K; Hettiarachchi, N; Hodson, J
Recent data suggest that azithromycin may not be as effective as doxycycline in eradication of genital chlamydial infection. The aim of this study was to compare the eradication rate of pharyngeal Chlamydia trachomatis infection after treatment with azithromycin 1 g stat with that of doxycycline 100 mg twice a day for seven days. A prospective open-label observational study was conducted on patients with pharyngeal Chlamydia trachomatis diagnosed at Whittall Street Clinic, University Hospitals Birmingham, Birmingham, UK, between July 2012 and July 2013. We confirmed eradication of pharyngeal Chlamydia trachomatis with a negative test of cure. We treated all our patients with azithromycin 1 g stat until February 2013. At that stage, we offered doxycycline to patients with pharyngeal Chlamydia trachomatis . A total of 398 patients (52 men, 346 women) were diagnosed with pharyngeal Chlamydia trachomatis during the study period. Of the 172 patients included in the final analysis, 78 were treated with azithromycin and 64 with doxycycline. Treatment failure was identified among 8/78 (10%) patients treated with azithromycin and 1/64 (2%) treated with doxycycline (absolute difference: 8 percentage points, 95% CI: 0–17%, p = 0.041). In our study, doxycycline 100 mg twice a day for seven days was associated with less treatment failure of oropharyngeal chlamydia compared with azithromycin 1 g stat . Future randomised studies should investigate whether patients with pharyngeal Chlamydia trachomatis should be followed up with a test of cure when treated with azithromycin, or be treated with doxycycline.